Identification of bacterial cells by chromosomal painting. - Lanoil, B D (1997)
Chromosomal painting is a technique for the microscopic localization of genetic material. It has been applied at the subcellular level to identify regions of eukaryotic chromosomes. Here we describe the development of bacterial chromosomal painting (BCP), a related technology for the identification of bacterial cells. Purified genomic DNAs from six bacterial strains were labeled by nick translation with the fluorochrome Fluor-X, Cy3, or Cy5. The average size of the labeled fragments was ca. 50 to 200 bp. The probes were hybridized to formaldehyde-fixed microbial cells attached to slides and visualized by fluorescence microscopy. In reciprocal comparisons, distantly related members of the class Proteobacteria (Escherichia coli and Oceanospirillum linum), different species of the genus Bacillus (B. subtilis and B. megaterium), and different serotypes of the subspecies Salmonella choleraesuis subsp. choleraesuis (serotype typhimurium LT2 and serotype typhi Ty2) could easily be distinguished. A combination of two probes, each labeled with a different fluorochrome, was used successfully to simultaneously identify two cell types in a mixture. Lysozyme treatment was required for the identification of Bacillus spp., and RNase digestion and pepsin digestion were found to enhance signal strength and specificity for all cell types tested. Chromosome in situ suppression, a technique that removes cross-hybridizing fragments from the probe, was necessary for the differentiation of the Salmonella serotypes but was not required to distinguish the more distantly related taxa. BCP may have applications in diverse branches of microbiology where the objective is the identification of bacterial cells.